Kontribusi Strategi Digital Marketing dan Layanan Digital terhadap Efektivitas UMKM Rumah Makan Fajwa Bangkinang - Dedi Kurnia; Rahmad Akbar (Politeknik Kampar, 2025)
This study was conducted to evaluate the extent to which digital marketing strategies and digital services contribute to improving the operational effectiveness of Micro, Small, and Medium Enterprises (MSMEs), particularly at Rumah Makan Fajwa located in Bangkinang. The research employed a quantitative approach, using data collection techniques through the distribution of questionnaires to selected respondents. To ensure data accuracy, quality tests were carried out, including validity tests, reliability tests, and classical assumption tests such as normality tests, heteroscedasticity tests, and multicollinearity tests. The data obtained were analyzed using descriptive and inferential analysis methods, which included multiple linear regression, t-tests to examine partial effects, F-tests to determine simultaneous effects, and the coefficient of determination to assess the contribution of independent variables to the dependent variable. The results of the analysis show that the implementation of digital marketing strategies significantly enhances the operational effectiveness of the MSME, Rumah Makan Fajwa. Similarly, the use of digital services has a notable impact in supporting the smoothness and efficiency of business operations. Overall, both digital marketing strategies and digital services jointly provide a significant positive contribution to the effectiveness of this MSME's business operations.